2022
DOI: 10.1186/s12864-022-08683-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the CIPK-CBL family gene and functional characterization of CqCIPK14 gene under drought stress in quinoa

Abstract: Background Calcineurin-like Protein (CBL) and CBL interacting protein kinase (CIPK) play a key role in plant signal transduction and response to various environmental stimuli. Quinoa, as an important plant with high nutritional value, can meet the basic nutritional needs of human Cash crop, is also susceptible to abiotic stress. However, CBL-CIPK in quinoa have not been reported. Results In this study, 16 CBL and 41 CIPK genes were identified in qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…This grouping is also reflected by their low intron number (less than three introns) and high intron number (more than ten introns). Moreover, this feature has also been reported in previous studies where CIPKs have been classified into two groups based on their intron structure [35,58]. It was stated that partial duplication probably has affected the intron number of gene family members [59].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This grouping is also reflected by their low intron number (less than three introns) and high intron number (more than ten introns). Moreover, this feature has also been reported in previous studies where CIPKs have been classified into two groups based on their intron structure [35,58]. It was stated that partial duplication probably has affected the intron number of gene family members [59].…”
Section: Discussionsupporting
confidence: 75%
“…Due to the importance of calcium-dependent signaling pathways, these gene families, CBL and CIPK, have been studied in various plants. 23 CBLs and 58 CIPK genes were identified from the genome of Medicago sativa [28], 27 CIPK genes from potato [30], 9 CBLs and 30 CIPK genes from the pecan genome [51], 10 CBLs and 26 CIPKs from Arabidopsis [17], 7 CBLs and 20 CIPK genes from bread wheat [52], 7 CBLs and 23 CIPK genes from canola [53], 16 CBLs and 41 CIPK genes from quinoa [35], and 20 CIPK genes from sugar beet [31]. The different number of members of this gene family suggests that they may have been subjected to evolutionary pressures differently in each plant [54,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CBL–CIPK gene family is composed of plant-specific and calcium signaling genes and is involved in indispensable signaling modules in various stress signaling pathways. The physiological functions of some CBL–CIPK pairs have been identified in a variety of plants [ 29 , 30 , 31 , 32 ], but less information on CBL–CIPK in peach trees has been reported. Therefore, the peach CIPK-CBL gene family members were identified by genome-wide bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that CIPK, or the CBL–CIPK complex, plays important roles in responses to environmental stresses [ 22 , 30 ]. For example, AtCIPK24 (SOS2) enables Arabidopsis to resist salt stress by interacting with AtCBL10 (SOS3) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%